UANG PANGOLAT (TEBUSAN) DALAM PERKAWINAN MASYARAKAT TOBING JULU - Risalan Basri Harahap (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2018)
There are habits that have been hereditary done in the implementation of marriage in society of Tobing Julu.That is giving money Pangolat (ransom), by the male (groom) to the “anak namboru” (anak namboru: a man who can marry a woman),which isrequsted by  “anak namboru” at the time of leavingwoman from her home to her husband's home. The ordinance of this request is done by inhibiting the two brides outside the yard of  woman’s house by preparing a seat and a drink, then invite the two brides to sit together, at the time they will enjoy the drinks that have been provided. But if it is seen and observed in the implementation of customs about money pangolat (ransom) committed by the community has largely deviated from the actual customary provisions. Based on that, the money pangolat (ransom) in the implementation of marriage in Tobing Julu Kec Huristak Padang Lawas District has done in accordance with the provisions of the actual and it is not contrary to Islamic law, then the law is allowed or ‘urf saheeh. On the contrary, if the execution of the pangolat money (ransom) has deviated from the true customary provisions, then the law is included in the fasid or rejected ‘urf